Selenium utilization during human lactation by use of stable-isotope tracers - Mangels, AR; Moser-Veillon, PB; Patterson, KY; Veillon, C (The American journal of clinical nutrition, 1990)
We examined utilization of selenomethionine (SeMet) and selenite in six lactating (L) and six nonlactating (NL) women, 2–3 mo postpartum, and seven never-pregnant (NP) women by use of stable-isotope tracers. All groups had similar selenium status at the start of the study. Significantly more selenium from SeMet than from selenite was absorbed and appeared in plasma in all groups. Milk contained more selenium from apparently absorbed SeMet than from selenite. More selenium from apparently absorbed selenite than from SeMet appeared in urine of NP and NL subjects whereas L subjects had approximately the same amount of selenium from apparently absorbed selenite and SeMet in their urine. All groups retained significantly more selenium from SeMet than from selenite; L women retained more selenium from selenite than did the other two groups. Absorption and retention of selenium from SeMet in L women did not appear to be significantly different from that in other women, suggesting that selenium requirements during lactation are increased mainly because of milk losses.